Association Between Systemic Disease And Presbycusis Among Patients Of Chronic Disease Management - Miska Mahira Majid; Rano Aditomo; Shelly Tjahjadewi; Andhika Dwi Anggara (International Journal of Health Engineering and Technology, 2026)
Presbycusis or age-related hearing loss significantly affects the quality of life of the elderly, with systemic diseases such as hypertension, diabetes mellitus, and dyslipidemia potentially accelerating its occurrence through vascular mechanisms. This study aims to analyze the relationship of these conditions to the occurrence of presbycusis in PROLANIS patients at the Kedungmundu Community Health Center. This observational analytical study with a cross-sectional design used 44 purposive samples aged ≥55 years. Data were collected through audiometry (ISO 1964 standard, bilateral >25 dB HTL) and medical record review, analyzed using the Chi-Square and Fisher's Exact tests (SPSS v.26, p<0.05). The results showed a prevalence of presbycusis of 68.2%, with a significant association for hypertension (p=0.000) and diabetes mellitus (p=0.006), but not for dyslipidemia (p=0.413). Hypertension and diabetes mellitus significantly increase the risk of presbycusis in PROLANIS patients, so routine audiometric screening in primary health facilities is necessary.